ELECTIVE COURSES IN ENGLISH AT TECHNICAL UNIVERSITY - Vladimir V. Volkhin; Tatyana A. Gertsen; Sofia B. Mayseles; Nina Yu. Lubimova (Moscow Polytechnic University, 2016)
The article presents the experience in organizing natural-scientific studies in English for chemical profile students. The purposes, features, forms of such studies are considered. These courses serve as the means to improve professionally oriented training of technical university students. Interdisciplinary connections are used in development of students' activity to apply knowledge and skills including the ability to use English proficiently in their professional environments.